The Civil Society of Ancient Rome - Anvar , Allamuratov (Indonesian Journal Publisher, 2024)
The article explores the Roman concept of civitas, which defined their society as a civil collective bound by shared rights, duties, politics, religion, and ideology. Cicero described civitas as encompassing common laws, justice, and social ties. Unlike Greek polis, Roman citizenship was managed by high magistrates like the censor, emphasizing a hierarchical structure. Roman voting operated on a